The rebel beneath the stairs eaudiobook - Holmes, EE (Riftmagic Saga, 2022)
Ashes, ashes, they'll all fall down . . . The death of a Resistance leader has thrown Post-Rift London into upheaval, and Eliza Braxton, a Riftborn lady's maid with exceptional magic, has promised her help to the rebel cause. But she quickly realizes that her role as a spy in the powerful Hallewell household will place her—and perhaps even those she loves—in near-constant peril. Resistance leader Eli Turner has concocted a new scheme which, if successful, will expose to the world the Illustratum's source of control over the Riftborn population, and Eliza agrees to play a crucial role in the plot. But as she dives into the dark and dangerous underbelly of Riftborn London, Eliza will discover truths she never imagined about her own life, and face decisions that will chart the course, not only of her own future, but of the whole Riftborn world. The spark has caught at last, and all that remains for Eliza, Eli, and their companions is to hope they can keep the inferno from consuming them all.